Exercise therapy for adolescent idiopathic scoliosis rehabilitation: a bibliometric analysis (1999–2023) - Ma, Run-Ting; Wu, Qiang; Xu, Zhen-Da; Zhang, Li; Wei, Yi-Xin; Gao, Qiang (Frontiers in Pediatrics, 2024)
Background Among the conservative treatments for rehabilitation of adolescent idiopathic scoliosis (AIS), exercise therapy has attracted a large number of studies as its advantages of good clinical effect, high operability, high compliance, few side effects and low cost. We conduct a bibliometric analysis of previous research to identify prevalent areas of study and inform research for the future directions in this paper. Methods Relevant publications and reviews were collected using the Science Citation Index Expanded from the Web of Science Core Collection. Information from the included studies was analyzed systematically using VOSviewer and Citespace software to identify patterns regarding publications, keywords, authors, citations, countries, institutions and journals. Results A total of 172 articles published from 1999 to 2023 were identified. Over the last decade, the number of publications has gradually increased, reaching a peak of 21 publications in 2021. China, North America and Western European countries and institutions are leading the way as far as the quantity of publications and the total number of citations are concerned. The current areas of focus are the efficacy of exercise therapy in relation to enhancing the quality of life of adolescents during rehabilitation. Conclusions This is the first bibliometric analysis that provides a comprehensive review of the research trends and advances in exercise therapy for the rehabilitation of AIS. The study identifies latest research frontiers and hot directions, providing a valuable reference for scholars in the field of exercise therapy.